Water soluble triblock and pentablock poly(methacryloyl nucleosides) from copper-mediated living radical polymerisation using PEG macroinitiators. (May 2015) - Garcia, Margarita; Beecham, Matthew P.; Kempe, Kristian; Haddleton, David M.; Khan, Afzal; Marsh, Andrew
Graphical abstract: Highlights: pMU–PEG 10 k–pMU and pMA–PEG 10 k–pMA by Cu-mediated living radical conditions. Pentablock pMA–pMU–PEG 10 k–pMU–pMA and pMU–pMA–PEG 10 k–pMA–pMU. Circular dichroism spectroscopy reveals order in pMA–PEG copolymers in water. New supramolecular structure between pMU–PEG 10 k–pMU and pMA–PEG 10 k–pMA in water. Abstract: The monomers methacryloyl uridine and methacryloyl adenosine have been polymerised under copper-mediated living radical conditions using poly(ethylene glycol) (PEG) macroinitiators to give triblock and pentablock copolymers of reasonable dispersity. The triblocks were used as initiators for the successful synthesis of pentablock copolymers. The secondary structures of the triblock and pentablock copolymers have been investigated using circular dichroism (CD) spectroscopy. The adenosine copolymers are found to exhibit more ordered secondary structures in water in comparison to the uridine derived polymers. New supramolecular structure is observed by CD upon mixing adenosine and uridine triblock copolymers in water. The polymers obtained are of interest as potential drug delivery agents through interaction with small molecules and oligonucelotides.